AUTOMATIC EXCHANGE OF INFORMATION DILIHAT DARI SUDUT PANDANG ACCOUNT REPRESENTATIVE (STUDI PADA KANTOR PELAYANAN PAJAK PRAMATA SURABAYA GUBENG DAN KANTOR PELAYANAN PAJAK MADYA SURABAYA) - ROSA LESTARI, LUSY (Jurnal Akuntansi AKUNESA, 2017)
Abstrak The implementation of Automatic Exchange of Information in 2017 is a system that supports the information exchange of the taxpayer accounts between countries. The aims of this study are to find out the knowledge and comprehension of Account Representatives towards the AEOI, the preparations which needed to be done and ,the benefits for Account Representatives from the AEOI based on studies in KPP Pratama Surabaya Gubeng and KPP Madya Surabaya. The method used in this study is the qualitative method which the data are taken from the results of the interviews. The results of this study showed that the Account Representatives had already known and understand about the AEOI. In KPP Pratama Surabaya Gubeng, there is still no preparation for the AEOI, however, KPP Madya Surabaya already made preparations although it is not maximum and is not reap the benefit because they didn’t implement the AEOI yet. Keywords : Automatic Exchange of Information System, preparation, Account Representative